2011
DOI: 10.1086/657331
|View full text |Cite
|
Sign up to set email alerts
|

How Credit Card Payments Increase Unhealthy Food Purchases: Visceral Regulation of Vices

Abstract: Some food items that are commonly considered unhealthy also tend to elicit impulsive responses. The pain of paying in cash can curb impulsive urges to purchase such unhealthy food products. Credit card payments, in contrast, are relatively painless and weaken impulse control. Consequently, consumers are more likely to buy unhealthy food products when they pay by credit card than when they pay in cash. Results from four studies support these hypotheses. Analysis of actual shopping behavior of 1,000 households o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
200
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(250 citation statements)
references
References 34 publications
10
200
2
2
Order By: Relevance
“…Where do we stand after 30 years of research on hedonic consumption? Awareness of the differences between hedonic and utilitarian products has provided a measure of predictability to researchers and practitioners wishing to address questions as diverse as how best to word advertising messages (e.g., Kronrod, Grinstein, & Wathieu, 2012), how the method and amount of payment affects the type of product one purchases and consumes (e.g., Bagchi & Block, 2011; Thomas, Desai, & Seenivasan, 2011), which situations prompt consumers to exert self‐determination (e.g., Botti & McGill, 2011), and which preferences might be heritable versus learned (Simonson & Sela, 2011). Researchers have also begun to build an understanding of how consumers recall and enjoy past hedonic consumption, and how they make predictions about their future enjoyment of products and experiences, with the hope that they can be encouraged to make choices that will make them happier in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Where do we stand after 30 years of research on hedonic consumption? Awareness of the differences between hedonic and utilitarian products has provided a measure of predictability to researchers and practitioners wishing to address questions as diverse as how best to word advertising messages (e.g., Kronrod, Grinstein, & Wathieu, 2012), how the method and amount of payment affects the type of product one purchases and consumes (e.g., Bagchi & Block, 2011; Thomas, Desai, & Seenivasan, 2011), which situations prompt consumers to exert self‐determination (e.g., Botti & McGill, 2011), and which preferences might be heritable versus learned (Simonson & Sela, 2011). Researchers have also begun to build an understanding of how consumers recall and enjoy past hedonic consumption, and how they make predictions about their future enjoyment of products and experiences, with the hope that they can be encouraged to make choices that will make them happier in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Participants selected from 21 food items shown with real brand names and pictures and were also told that the brand names shown were examples and that if they wanted another brand they should still select the item. This task was adapted from the one that Thomas, Desai, and Seenivasan (2011) used to examine the effect of payment mode (cash vs. credit) on preference for hedonic (vs. utilitarian) food items. Thomas et al found that payment method affects hedonic (lower preference with cash) but not utilitarian preference.…”
Section: Dependent Variable Food Choice Taskmentioning
confidence: 99%
“…We conducted two separate regression analyses for the hedonic and utilitarian totals with categorization flexibility index as the independent variable in each. Thomas et al (2011), the source of our dependent variable, also used separate regressions. The hedonic total (M = 3.33) was the dependent variable in the first, and the categorization flexibility index positively affected it (β = 0.06, t(57) = 2.63, p b .05); the utilitarian total (M = 5.22) was the dependent variable in the second, and the categorization flexibility index did not affect it (β = − 0.02, t(57) = − 0.68, p = .50).…”
Section: Test Of H1mentioning
confidence: 99%
“…Thus, when the available credit is low, consumers with greater self-control increase spending, but when the available credit is high, they reduce spending (Wilcox, Block & Eisenstein, 2011). Thomas, Desai and Seenivasan (2011) in a study are of view that the pain of paying in cash can curb impulsive urges to purchase products like unhealthy food. Credit card payments, in contrast, are relatively painless and weaken impulse control.…”
Section: Review Of Literaturementioning
confidence: 99%